Nutrition and Weight Management Knowledge, Lifestyle Factors, Dietary Intake and Body Weight Status of Iranian Postgraduate Students in Universiti Putra Malaysia - Zarei, Fatemeh (2011)
A cross-sectional study was conducted to determine factors associated with body weight status among Iranian adolescents in Secondary and High Schools run by the Embassy in Kuala Lumpur. Out of the 296 respondents, 150 (50.3%) were male and 146 (49.3%) were female. Height and weight were taken and body mass index (BMI) was calculated. Results showed that 18.6% and 23.6% of adolescents were severe thin and thin, while 14.5% and 11.1% were overweight and obese respectively. Almost one third (32.1%) of them had normal BMI. Body weight status was found to be significantly associated with age (r=0.23, p<0.05), gender (χ2 =11.18, p< 0.05) and grade (χ2=34.172, p<0.05) Physical Activity Questionnaire for children (PAQ-C) and adolescents (PAQ-A) used to assess physical activity found more than half of the respondents in the low, 14.5% in the moderate and only 4.7% of the respondents were in high physical activity level. Males had significantly higher physically activity scores than females (p<0.05) but there was no significant association between body weight status and physical activity level. Three-quarters 75% of the respondents had breakfast daily while 25% had never had breakfast. The most frequently consumed foods items include cooked oil, rice, white bread, chips, sandwich, tea, meat. Fruits, milk and most of vegetables among the foods less frequently consumed. Because Dietary Reference Intake (DRIs) was different by age groups respondents were separated into two groups (11 to 13 and 14 to 17) by age. In both groups the energy, carbohydrate and protein intakes were lower than DRIs. Intake of all micronutrients among in both age groups and sexes were found to be higher than DRI, except vitamins B1, B2, C, D and E, folate, zinc, magnesium, potassium, calcium and phosphorus. Only 39.5% of the respondents correctly estimated their own weight status while 9.8% under estimated their weights and 50.7% who overestimated their weights. Significantly more males correctly estimated their weights than females. There was a tendency for the females to overestimate their weight and therefore it was not surprising that 72.6% of them expressed their desire to lose weight while 60% of the males wanted to gain weight. There was significant association between body weight status and perception of ideal body size (r=0.269 and p=0.000) and healthy body size (r=0.250, p=0.000). In this instance more respondents with body weight status in the severe thinness and thinness categories like to have a bigger body size compared to the respondents who were overweight and obese. No significant association was found between their perception of the current body size and body weight status. In general more females desired a smaller body size than males who more often expressed the desire to have a bigger body size. Multiple regression analyses showed that age and physical activity contributed significantly to the prediction of 10% of the variance of body weight status among the respondents. This study provides some information for the Iranian Secondary and High School to undertake intervention programs to improve the body weight status of their students.